ANALYSIS OF STUDENT LEARNING ACTIVITIES IN SCIENCE LEARNING USING INQUIRY MODEL BASED ON LOCAL WISDOM - Encep Andriana; Endang Widya Ningsih; Nana Hendracipta; Mudmainah Vitasari; Callista Aulina (Department of Primary education, Faculty of Teacher Training and Education, Universitas Su, 2020)
This research was aims to analyze the students’ learning activity based on local wisdom using inquiry model on science subjects. The type of this research is descriptive-quantitatve. The object of this research is the 4th grade students of SDN Banjar Agung 4 with the total of 29 students. The instrument used in this research is observation sheets of students’ learning activities. The final result of this study is an analysis of student learning activity indicators using a local-wisdom based learning model that has been developed previously that obtained the average score of student learning activities is 76.2% with “Good” category and the average score of learning implementation is 96% well implemented. Keywords: local wisdom; inquiry model